If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9p + 4 = 8p + 8 Reorder the terms: 4 + 9p = 8p + 8 Reorder the terms: 4 + 9p = 8 + 8p Solving 4 + 9p = 8 + 8p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-8p' to each side of the equation. 4 + 9p + -8p = 8 + 8p + -8p Combine like terms: 9p + -8p = 1p 4 + 1p = 8 + 8p + -8p Combine like terms: 8p + -8p = 0 4 + 1p = 8 + 0 4 + 1p = 8 Add '-4' to each side of the equation. 4 + -4 + 1p = 8 + -4 Combine like terms: 4 + -4 = 0 0 + 1p = 8 + -4 1p = 8 + -4 Combine like terms: 8 + -4 = 4 1p = 4 Divide each side by '1'. p = 4 Simplifying p = 4
| 7(n+2)-3n=4+4n+10 | | 5y-9=96 | | 1x+3x= | | 6(1-3x)-2(2x-1)=18x | | 2.5n=-20 | | 9x-10y=3 | | 3s-8=9 | | 5n+3n+n+5=26 | | 5y=12x-5 | | 3x+9=56-4x | | 3a-b=1 | | a+10=27 | | 10x+1y=8 | | -5(1-5)+(-8x-2)=4x-8x | | -1/2+w=3/5 | | (x-6)+x= | | 23+2x=13 | | 3(2c+3)=2(3c-4) | | 6n-10+4n=-18+10n+14 | | 51-3x=6x+23 | | a+3b=7 | | 13+2x=x+25 | | 3x-18/15 | | 5=4n-6 | | 3w-40-2w+60+w= | | 13x+12=38 | | 4n-6=14 | | 15-12x=51 | | f(x)=10-4x | | 4x+18=x+33 | | -31/3b+b | | 8+6a=-28+24 |